2021
DOI: 10.3390/antiox10030416
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Fumarate, an Approved Multiple Sclerosis Treatment, Reduces Brain Oxidative Stress in SIV-Infected Rhesus Macaques: Potential Therapeutic Repurposing for HIV Neuroprotection

Abstract: Dimethyl fumarate (DMF), an antioxidant/anti-inflammatory drug approved for the treatment of multiple sclerosis, induces antioxidant enzymes, in part through transcriptional upregulation. We hypothesized that DMF administration to simian immunodeficiency virus (SIV)-infected rhesus macaques would induce antioxidant enzyme expression and reduce oxidative injury and inflammation throughout the brain. Nine SIV-infected, CD8+-T-lymphocyte-depleted rhesus macaques were studied. Five received oral DMF prior to the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 103 publications
(146 reference statements)
0
13
0
Order By: Relevance
“…Dimethyl fumarate (DMF) is a methyl ester synthesized through the esterification of fumaric acid. Recently, DMF has been shown to exert neuroprotective and immunomodulatory effects associated with endogenous antioxidant mechanisms and mitigation of oxidative stress in in vivo models [147,148].…”
Section: Dimethyl Fumaratementioning
confidence: 99%
“…Dimethyl fumarate (DMF) is a methyl ester synthesized through the esterification of fumaric acid. Recently, DMF has been shown to exert neuroprotective and immunomodulatory effects associated with endogenous antioxidant mechanisms and mitigation of oxidative stress in in vivo models [147,148].…”
Section: Dimethyl Fumaratementioning
confidence: 99%
“…DMF has been approved for the treatment of multiple sclerosis and might also protect against systemic and central nervous system complications in HIV infection ( Gill and Kolson, 2013 ). In a study on rhesus macaques infected with simian immunodeficiency virus, treatment with DMF limited the oxidative stress throughout the brain ( Garcia-Mesa et al, 2021 ). Olagnier et al demonstrated that DMF inhibits SARS-CoV-2 replication and the expression of associated inflammatory genes, thus proposing that DMF could be repurposed as a small molecule inhibitor of SARS-CoV-2 replication and inflammation-associated pathology in COVID-19 patients ( Olagnier et al, 2020 ; Timpani and Rybalka, 2021 ) ( Figure 2 ).…”
Section: Fumarate and Its Role In Viral Infectionmentioning
confidence: 99%
“…Thus, protective therapies that aim at suppressing these pathologic pathways would be desirable. In a recent study the ability of dimethyl fumarate (DMF), an antioxidant/anti-inflammatory drug approved for the treatment of multiple sclerosis, has been examined in a rhesus macaque SIV infection model [ 113 , 114 ]. In various animal models, activation of nuclear factor erythroid 2–related factor 2 (Nrf2)/ARE pathway by DMF in the brain is associated with reduced neurodegeneration, and may promote axonal regeneration and block neurotoxicity [ 115 , 116 ].…”
Section: Innovative Therapeutic Approachesmentioning
confidence: 99%
“…In various animal models, activation of nuclear factor erythroid 2–related factor 2 (Nrf2)/ARE pathway by DMF in the brain is associated with reduced neurodegeneration, and may promote axonal regeneration and block neurotoxicity [ 115 , 116 ]. In a CD8+ T lymphocyte depletion model of SIV neuro-pathogenesis, rhesus macaques received oral DMF prior to SIV infection and through to the necropsy day [ 114 ]. Global brain responses to DMF treatment, such as higher brain expression of antioxidant enzymes, lower DNA and protein oxidation, and a more reduced redox state is observed in SIV-infected treated animals as compared to the untreated.…”
Section: Innovative Therapeutic Approachesmentioning
confidence: 99%
See 1 more Smart Citation